(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: Continental values in northwestern Libya are affected by several factors, the most important of which are the daily and monthly temperature range, the location in relation to the sea, and the elevation of the place below sea level. However, the change in continental features reflected the change in the thermal range, although this change was not obvious. In the months, the temperature range was highest in February, and it was very low in November. Sabratha is the least continental region. In contrast, the most important continental region was Nalut region in the range of the Western Mountain. Using the Borisov and Khormov equations, the results of the values of the two equations draw a line in time and place, which reduces the value of their different elements in calculating the values of the continent.